Dari Warisan Kolonial ke Modernisasi Militer: Relokasi Pangkalan Udara Morokrembangan ke Juanda (1949–1964) - Jihan Nabilah Raharjo; Esa Putra Bayu Gusti Gineung Patridina (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
Morokrembangan was a maritime air base inherited from the Dutch colonial administration and played a significant role in the development of the Indonesian Navy's aviation. Following Indonesia's independence, the base continued to be utilized by the Indonesian Navy (ALRI). However, inadequate facilities, geographical limitations, and the evolving demands of national defense rendered Morokrembangan increasingly unsuitable, prompting the relocation of the naval air base to Juanda, which was officially inaugurated in 1964 as part of Indonesia's maritime defense modernization. This study aims to analyze the factors underlying the relocation of the Indonesian Navy's air base from Morokrembangan to Juanda and to examine its impact on naval aviation during the early years of Indonesia's independence. The research employs the historical method, consisting of four stages: heuristics, source criticism, interpretation, and historiography. Research data were collected from archival records, government documents, newspapers, interviews, historical photographs, and relevant literature. The findings reveal that the relocation of the air base to Juanda was not merely the transfer of a military facility but also an integral component of the state's defense modernization strategy aimed at enhancing the infrastructure and operational capabilities of Indonesian naval aviation. Furthermore, the relocation contributed to the organizational development of the Navy and strengthened Indonesia's maritime air capabilities. This study concludes that the relocation of the naval air base from Morokrembangan to Juanda marked a significant milestone in the transformation of Indonesian naval aviation toward a more modern and strategically capable maritime defense force.